2016
DOI: 10.1074/jbc.m115.705012
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecular Allosteric Activator of the Sarco/Endoplasmic Reticulum Ca2+-ATPase (SERCA) Attenuates Diabetes and Metabolic Disorders

Abstract: Dysregulation of endoplasmic reticulum (ER) Ca2؉ homeostasis triggers ER stress leading to the development of insulin resistance in obesity and diabetes. Impaired function of the sarco/endoplasmic reticulum Ca 2؉ -ATPase (SERCA) has emerged as a major contributor to ER stress. We pharmacologically activated SERCA2b in a genetic model of insulin resistance and type 2 diabetes (ob/ob mice) with a novel allosteric activator, CDN1163, which markedly lowered fasting blood glucose, improved glucose tolerance, and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
159
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(170 citation statements)
references
References 49 publications
(48 reference statements)
8
159
3
Order By: Relevance
“…Although tissue-specific deletion models are needed to fully resolve the effects of SERCA2 loss on β-cell function and peripheral insulin sensitivity, our data and those of others suggest that strategies aimed at restoration of SERCA2 expression and/or modulation of SERCA2 activity represent viable strategies to improve glucose homeostasis (24,28,30). Finally, these data also have relevance for humans with Darier-White disease, in which one copy of the ATP2A2 gene is defective.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although tissue-specific deletion models are needed to fully resolve the effects of SERCA2 loss on β-cell function and peripheral insulin sensitivity, our data and those of others suggest that strategies aimed at restoration of SERCA2 expression and/or modulation of SERCA2 activity represent viable strategies to improve glucose homeostasis (24,28,30). Finally, these data also have relevance for humans with Darier-White disease, in which one copy of the ATP2A2 gene is defective.…”
Section: Discussionmentioning
confidence: 66%
“…Previous in vitro experiments have also shown that SERCA2 and SERCA1 interact with insulin receptor substrate 1 and 2 in skeletal muscle in an insulin-dependent manner, suggesting an effect of SERCA activity on glucose uptake (29). Furthermore, in vivo adenoviral-mediated restoration of SERCA2b expression in the liver improved glucose homeostasis in obese mice (24,28), whereas treatment with the SERCA activator CDN1163 improved hepatic ER stress and glucose tolerance in the ob / ob mouse model (30). In our study, however, S2HET and control mice exhibited indistinguishable patterns of weight gain, body composition, and systemic and tissue-specific insulin sensitivity, suggesting that the glucose intolerance observed in the HFD-fed S2HET mice did not arise from perturbations in adiposity or insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress might also integrate signals derived from enlarged adipocytes, which release higher amounts of FFAs [69]. Administration of chaperons or small molecules which decrease ER stress has been shown to reduce adipose tissue inflammation, improve insulin sensitivity and metabolic disorders [70,71]. Therefore, targeting adipose tissue stress and reversing adipose tissue inflammation and its related metabolic abnormalities may hold promise as a future therapeutic strategy in the treatment of type 2 diabetes.…”
Section: Role Of Cellular Stress In Adipose Tissue Inflammationmentioning
confidence: 97%
“…In wild-type p53 tumors, direct p53 activators might be of use. Other solace may come from SERCA-activating small molecules like CDN1163 [54], provided these agents can be delivered to tumor cells while sparing healthy cells [52].…”
Section: Intracellular Camentioning
confidence: 99%
“…In wild-type p53 tumors, direct p53 activators might be of use. Other solace may come from SERCA-activating small molecules like CDN1163 [54], provided these agents can be delivered to tumor cells while sparing healthy cells [52].These recent papers highlight that deregulation of IP 3 R3 ubiquitination homeostasis not only impacts death and survival of cells but also contributes to the oncogenic behavior of cells with dysfunctional tumor suppressors by either (i) lacking PTEN [36] or by (ii) displaying deficiencies in BAP1 [47]. They underpin the emerging role of altered Ca 2+ signaling at the MAM level as a key event in apoptosis resistance that contributes early events associated with oncogenesis and tumor formation.…”
mentioning
confidence: 99%